Students' responses to scenarios depicting ethical dilemmas: a study of pharmacy and medical students in New Zealand. Issue 7 (6th May 2016) - Henning, Marcus A; Malpas, Phillipa; Ram, Sanya; Rajput, Vijay; Krstić, Vladimir; Boyd, Matt; Hawken, Susan J
Abstract : One of the key learning objectives in any health professional course is to develop ethical and judicious practice. Therefore, it is important to address how medical and pharmacy students respond to, and deal with, ethical dilemmas in their clinical environments. In this paper, we examined how students communicated their resolution of ethical dilemmas and the alignment between these communications and the four principles developed by Beauchamp and Childress. Three hundred and fifty-seven pharmacy and medical students (overall response rate=63%) completed a questionnaire containing four clinical case scenarios with an ethical dilemma. Data were analysed using multiple methods. The findings revealed that 73% of the qualitative responses could be exclusively coded to one of the 'four principles' determined by the Beauchamp and Childress' framework. Additionally, 14% of responses overlapped between the four principles (multiple codes) and 13% of responses could not be coded using the framework. The subsequent subgroup analysis revealed different response patterns depending on the case being reviewed. The findings showed that when students are faced with challenging ethical dilemmas their responses can be aligned with the Beauchamp and Childress framework, although more contentious dilemmas involving issues of law are less easily categorised. The differences between year and discipline groups show students are developing ethical frames of reference that may be linked with their teaching environments and their levels of understanding. Analysis of these response patterns provides insight into the way students will likely respond in 'real' settings and this information may help educators prepare students for these clinical ethical dilemmas.